(untitled) (Bangladesh Journal of Medical Science, 2023)
Objective: Abnormal uterine bleeding (AUB) is an often pathology in women of reproductive age. Materials and methods. The retrospective analysis of 336 patients with AUB was performed between 2017-2020. We analyzed the social and demographic data, reproductive function, somatic diseases, type and causes of AUB. Results. According to PALM-COEIN classification polyps were found in 13.39 % of patients, adenomyosis – 20.83 %, leiomyoma – 37.50 %, malignancy/hyperplasia – 14.29 %, ovulation disorders – 24.11 %, endometrial factor – 12.20 %, iatrogenic reason – 6.25 %. Conclusion. PALM-causes dominate over COEINetiological factors in the development of AUB in women of reproductive age. But, there are some differences in the rate of causes according to the age period. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 809-814